(untitled) (Bangladesh Journal of Nutrition, 2015)
A cross-sectional study was carried out to investigate the prevalence of overweight among adolescent school girls in Dhaka City and examine the relationship of various socio-economic factors with overweight. A total of 130 girls aged 12 to 16 years of three girls high schools were selected by random sampling. Height and weight were measured to calculate body mass index (BMI). Dietary intake was estimated using 24 hour recall method. The usual pattern of food intake was examined using a 7 -day food frequency questionnaire. Prevalence of overweight was denoted by BMI above 85th percentile. In this study 33.1% of the participants were overweight and the rest were found to be normal. Participants were divided into two groups-normal weight participants with a BMI between 5th and 85th percentile and overweight participants with a BMI above 85th percentile of WHO/NCHS reference values. Mean intake of energy and all nutrients, except vitamin C were found significantly higher in overweight girls compared to normal weight girls. Overwhelming majority (95%) of the overweight girls consumed fast foods, soft drinks (44%) and fruit juice (21 %) more than 3 times/week. Consumption of these foods by overweight girls was significantly higher than that of normal weight girls. Significant positive relationship was found among overweight and monthly family income, educational level of the parents and consumption of fast-food, soft drinks, fruit juice and energy intake but inverse relationship was found between overweight and participant’s family size.